Granulin: an invasive and survival-determining marker in colorectal cancer patients - Klupp, Fee; Kahlert, Christoph; Franz, Clemens; Halama, Niels; Schleußner, Nikolai; Wirsik, Naita Maren; Warth, Arne; Schmidt, Thomas; Ulrich, Alexis (International journal of molecular sciences, 2021)
Background: Granulin is a secreted, glycosylated peptide—originated by cleavage from a precursor protein—which is involved in cell growth, tumor invasion and angiogenesis. However, the specific prognostic impact of granulin in human colorectal cancer has only been studied to a limited extent. Thus, we wanted to assess the expression of granulin in colorectal cancer patients to evaluate its potential as a prognostic biomarker. Methods: Expressional differences of granulin in colorectal carcinoma tissue (n = 94) and corresponding healthy colon mucosa were assessed using qRT-PCR. Immunohistochemistry was performed in colorectal cancer specimens (n = 97), corresponding healthy mucosa (n = 47) and colorectal adenomas (n = 19). Subsequently, the results were correlated with histopathological and clinical patients’ data. HCT-116 cells were transfected with siRNA for invasion and migration assays. Results: Immunohistochemistry and qRT-PCR revealed tumoral over expression of granulin in colorectal cancer specimens compared to corresponding healthy colon mucosa and adenomas. Tumoral overexpression of granulin was associated with a significantly impaired overall survival. Moreover, downregulation of granulin by siRNA significantly diminished the invasive capacities of HCT-116 cells in vitro. Conclusion: Expression of granulin differs in colorectal cancer tissue, adenomas and healthy colon mucosa. Furthermore, granulin features invasive and migrative capabilities and overexpression of granulin correlates with a dismal prognosis. This reveals its potential as a prognostic biomarker and granulin could be a worthwhile molecular target for individualized anticancer therapy.
Gesehen am 05.08.2021